2014
DOI: 10.14417/ap.870
|View full text |Cite
|
Sign up to set email alerts
|

As relações de pares de jovens socialmente retraídos

Abstract: O presente estudo tem como objetivo caracterizar as relações sociais de adolescentes socialmente retraídos, quer com o seu grupo de pares, quer com os seus melhores amigos. Os dados foram recolhidos com base em 3 instrumentos: o Extended Class Play -que permite aceder às avaliações que os pares fazem do comportamento, funcionamento e reputação sociais dos colegas -, as Nomeações de Amizade -que permite identificar quem são os melhores amigos -e o Questionário da Qualidade da Amizade -destinado a aceder às perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(50 reference statements)
3
5
0
Order By: Relevance
“…Furthermore, our results illustrated that anxiously withdrawn victims were considered significantly less aggressive by their peers than both victimized adolescents who did not exhibit anxious withdrawn behaviors and non-victimized adolescents. In line with previous findings (e.g., Haynie et al, 2001;Schwartz et al, 2001;Veenstra et al, 2005;Leary et al, 2006;Correia et al, 2014b), anxiously withdrawn victims represented a subgroup of youths who responded passively and nonaggressively to peer victimization. By avoiding or withdrawing from social interaction and displaying shy and submissive behaviors, anxiously withdrawn adolescents may be perceived as vulnerable targets for peer maltreatment, because they are unlikely to retaliate against aggressors (Rubin et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, our results illustrated that anxiously withdrawn victims were considered significantly less aggressive by their peers than both victimized adolescents who did not exhibit anxious withdrawn behaviors and non-victimized adolescents. In line with previous findings (e.g., Haynie et al, 2001;Schwartz et al, 2001;Veenstra et al, 2005;Leary et al, 2006;Correia et al, 2014b), anxiously withdrawn victims represented a subgroup of youths who responded passively and nonaggressively to peer victimization. By avoiding or withdrawing from social interaction and displaying shy and submissive behaviors, anxiously withdrawn adolescents may be perceived as vulnerable targets for peer maltreatment, because they are unlikely to retaliate against aggressors (Rubin et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, and in line with our results, previous research has demonstrated that victims of peer maltreatment feel lonelier, less happy, and have fewer good friends at school than their peers (Boulton and Underwood, 1992 ; Nansel et al, 2001 , 2004 ). Furthermore, the lack of proper opportunities for anxiously withdrawn victimized adolescents to interact within the peer group and develop significant relationships at school (Haynie et al, 2001 ; Schwartz et al, 2001 ; Veenstra et al, 2005 ; Leary et al, 2006 ; Correia et al, 2014b ) may be linked to heightened feelings of loneliness. It is important to note, however, that these feelings of loneliness did not extend to the family environment.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the long-term consequences of high and stable BI/SW during early childhood, the descriptions of psychologists in Portugal are also consistent with Rubin's developmental and transactional model (Rubin et al, 2009). Due to low emotional, social and socio-cognitive competencies, our participants acknowledge that children who continue to display socially wary behaviors over time are more likely to internalize negative thoughts and feelings about the self (i.e., negative comparisons with peers about their social and performance skills), to experience later difficulties in establishing appropriate social interactions and, ultimately, peer exclusion and victimization (Correia et al, 2014;. Given the salience of sociability in Southern European cultures (Casiglia et al, 1998), BI/SW may be viewed as especially deviant from social norms and expectations for social relationships and may evoke particularly negative peer reactions Rubin et al, 2009).…”
Section: Perceptions Of Portuguese Psychologists About the Consequences Of Bi/sw For Child's Socioemotional Adjustmentsupporting
confidence: 75%
“…Due to low emotional, social and socio-cognitive skills, the developmental and transactional model (Rubin et al, 2009) establishes that children who continue to display socially wary behaviors over time are more likely to experience later peer exclusion and victimization (Correia, Santos, Freitas, Ribeiro, & Rubin, 2014;Rubin, Barstead, Smith, & Bowker, 2018) and to display poorer teacher-rated academic performance skills than their peers, due to their lower academic engagement in the classroom (Kalutskaya, Archbell, Rudasill, & Coplan, 2015). Furthermore, the recognition of low emotional, social and socio-cognitive skills over time may lead withdrawn children to internalize negative self-cognitions, increasing their vulnerability for the development of later social anxiety and depression .…”
mentioning
confidence: 99%
“…Recent Portuguese empirical studies (Santos et al, 2015) and US-Portugal comparisons (Vaughn et al, 2016) have shown that preschoolers who displayed low social engagement were less visible for peers and less likely to be chosen as preferred playmates by peers. Associations between AW and sociometric measures of negative peer outcomes have been also observed among Portuguese adolescents (Correia, Santos, Freitas, Ribeiro, & Rubin, 2014). However, prosocial behaviors have appeared to play an especially relevant protective role against the negative peer outcomes that have been typically associated with AW (Freitas, Santos, Ribeiro, Daniel, & Rubin, 2019), reflecting possibly the salience of values related to solidarity, equality and support to others in Portugal (European Commission, 2012).…”
Section: The Influence Of Culture On Peer Attitudes and Responses Towmentioning
confidence: 96%